การประเมินประสิทธิภาพเชื้อราในดินต่อการควบคุมไส้เดือนฝอยรากปม Meloidogyne incognita สาเหตุโรครากปมพริกในแปลงปลูกพืชขนาดเล็ก - ยุวดี ชูประภาวรรณ ยุวดี ชูประภาวรรณ; วีระศักดิ์ ศักดิ์ศิริรัตน์ วีระศักดิ์ ศักดิ์ศิริรัตน์; อนันต์ หิรัญสาลี อนันต์ หิรัญสาลี; นิวัฒ เสนาะเมือง นิวัฒ เสนาะเมือง (วารสารแก่นเกษตร, 2007)
-